Transcriptional Regulation of the Streptococcus salivarius 57.I Urease Operon - Chen, Yi-Ywan M. (American Society for Microbiology, 1998)
The Streptococcus salivarius 57.I ure cluster was organized as an operon, beginning with ureI, followed by ureABC (structural genes) and ureEFGD (accessory genes). Northern analyses revealed transcripts encompassing structural genes and transcripts containing the entire operon. A ς(70)-like promoter could be mapped 5′ to ureI (PureI) by primer extension analysis. The intensity of the signal increased when cells were grown at an acidic pH and was further enhanced by excess carbohydrate. To determine the function(s) of two inverted repeats located 5′ to PureI, transcriptional fusions of the full-length promoter region (PureI), or a deletion derivative (PureIΔ100), and a promoterless chloramphenicol acetyltransferase (CAT) gene were constructed and integrated into the chromosome to generate strains PureICAT and PureIΔ100CAT, respectively. CAT specific activities of PureICAT were repressed at pH 7.0 and induced at pH 5.5 and by excess carbohydrate. In PureIΔ100CAT, CAT activity was 60-fold higher than in PureICAT at pH 7.0 and pH induction was nearly eliminated, indicating that expression was negatively regulated. Thus, it was concluded that PureI was the predominant, regulated promoter and that regulation was governed by a mechanism differing markedly from other known mechanisms for bacterial urease expression.